IVUmed: A Nonprofit Model for Surgical Training in Low-Resource Countries - Mohamed Jalloh; Joshua P. Wood; Mary Fredley; Catherine R. deVries (Ubiquity Press, 2015)
Background: Low- and middle-income countries (LMICs) face both training and infrastructural challenges for surgical care, particularly for specialty care, such as for urology. Practitioners charged with caring for these patients have few options for basic or advanced training. Objectives: IVUmed, a nonprofit organization, has for 20 years supported urological educational programs in 30 LMICs by coordinating a network of US and international academic and private providers, institutions, industry partners, and professional societies. Methods: IVUmed's motto, "Teach One, Reach Many" has emphasized a teach-the-teacher approach. Program partners, such as Hopital General de Grand Yoff in Dakar, Senegal, have advanced from little urological subspecialty availability to having the capacity to treat a wide range of conditions while also teaching surgeons from Senegal and neighboring countries. Conclusions: Long-term program commitments; effective communication; and a shared vision among the program site, the coordinating nongovernmental organization, and supporting organizations facilitate the development of thriving surgical teaching programs capable of serving local communities and conducting outreach training.